Pengaruh Adaptasi Karir terhadap Kinerja Karyawan melalui Kepuasan Kerja - Dewi Lestari (Jurnal Ilmu Manajemen, 2021)
Every company strives to improve employee performance to achieve the goals set by the company. To achieve this goal, companies need employees who have good performance. This study analyses the relationship between career adaptation and employee performance through job satisfaction in the Savings and Loans Unit of KUD Minatani Brondong employees. This type of research is quantitative research using a saturated sample technique. The object used for this research sample is the KUD Minatani Savings and Loans Unit Brondong, amounting to 51 respondents. From the statistical analysis results, this study uses Partial Least Square (PLS) and is assisted by smartPLS 3.0 software. This study indicates that the results of career adaptability have a relationship with job satisfaction and employee performance, the variable job satisfaction has a relationship with performance, and job satisfaction has a direct relationship between career adaptability and employee performance. The research implies there is a form of good teamwork and fair leadership to employees in their careers. In addition, the organization provides support in the form of work facilities to make employees feel satisfied, comfortable, safe while working so that it can have an impact on performance.